Wakaf Produktif di Yayasan Addin As-Shiddieq Pacitan Perspektif Total Quality Management (TQM) - Nur Alfiyan, Wahyu; Prasetiyo, Luhur (Invest Journal of Sharia & Economic Law, 2021)
Pondok Pesantren Addin As Shiddieq as a social institution seeks to provide benefits to the people through the management of productive waqf. However, the management of this waqf has not been properly managed like other productive waqf organizations. The organizational structure of the productive waqf management of the Addin As Shiddieq Foundation only consists of nadzir and managers of the waqf assets. Based on these facts, this paper intends to look at the productive waqf management at the Addin As-Shiddieq Islamic Boarding School according to Total Quality Management and its impact on waqf productivity and on society. This research uses qualitative research methods. The data obtained were then analyzed using the characteristics of Total Quality Management (TQM). Of the five criteria mentioned by MA Mannan, the productive waqf management of the Addin As Shiddieq Foundation still has weaknesses at point 4, which is to record everything related to the beneficiary. Meanwhile, in terms of impact, the productive waqf management carried out by the Addin As Shiddieq Foundation has had a positive impact, both on the productivity of waqf assets and on the community.